PELAKSANAAN SUPERVISI KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU PENDIDIKAN AGAMA ISLAM DI SD AR RAUDAH KOTA BANDAR LAMPUNG TAHUN AJARAN 2024/2025 - DEWI, TRI UTAMI (UNISAN JURNAL, 2025)
This research aims to explore the implementation of supervision conducted by the school principal to improve the performance of Islamic Education teachers at SD Ar Raudah, Lampung City in the 2024/2025 academic year. The research method used was descriptive qualitative with a case study approach. Data were collected through interviews, observations, and documentation. The results of the study indicate a significant relationship between the implementation of the principal’s supervision and the improvement of teachers’ performance. The interventions carried out through supervision were effective in providing motivation and support for teachers, especially in facilitating their professional development. This study also identifies several challenges faced by principals in implementing supervision, including lack of time and resources. Recommendations are proposed to improve the quality of supervision through training for principals and the development of a better monitoring system. Keywords: supervision, school principal, teacher performance, Islamic education, primary education.